Driving factors affecting zooplankton functional groups in a shallow eutrophic lake - Sorguç Bura Uğur; Demirkalp Fatma Yıldız; Saygı Yasemin (Oceanological and Hydrobiological Studies)
The important role of zooplankton in linking different trophic levels has been the subject of extensive research, highlighting their crucial contribution to aquatic ecosystems and energy flow. Classification of organisms into functional groups using a method that combines taxonomic assessments with direct functional measurements is very effective in understanding their interactions with the environment. Our objective was to determine the seasonal changes of zooplankton in Lake Yeniçağa using zooplankton functional groups. A total of 19 zooplankton species were identified in the lake and classified into six functional groups. Medium-sized cladoceran and copepod carnivorous feeders (MCC) accounted for 45.74% of all functional groups and were the dominant group in the lake. Throughout the year, medium and large zooplankton generally dominated in the lake, with smaller functional groups briefly dominating in spring and autumn. Statistical analysis indicates that medium-sized cladoceran and copepod filter feeders (MCF) and large-sized cladoceran and copepod filter feeders (LCF) showed a positive relationship with Secchi depth and a negative relationship with chlorophyll a. Other groups exhibited relatively lower correlations with environmental parameters. It can be concluded that the observed seasonal changes in these groups are affected not only by environmental parameters, but also by the availability of food resources.